Protease in sturgeon sperm and the effects of protease inhibitors on sperm motility and velocity - Alavi, Sayyed Mohammad Hadi; Postlerová-Maňásková, Pavla; Hatef, Azadeh; Pšenička, Martin; Pěknicová, Jana; Inaba, Kazuo; Ciereszko, Andrzej; Linhart, Otomar (Fish physiology and biochemistry, 2014)
In mammals, proteases are present in sperm acrosome and play key role in fertilization. Sturgeon sperm has an acrosome, but its physiology, biochemistry, and potential role in fertilization are unknown. In the present study, we have observed high protease activity in acidic extract of intact sperm compared to that of seminal plasma in sterlet (Acipenser ruthenus). The protease activity was decreased and increased in acidic extract of motility-activated sperm and in the activation medium, respectively. Molecular analysis revealed total protease and serine (acrosin) protease activities in sperm acidic extract which was accumulated in a protein band with relative molecular mass of 35 kDa. Immunoelectron microscopy using an affinity-purified polyclonal antibody for boar acrosin localized the protease at the acrosome region. Moreover, initiation of sperm motility was inhibited after activation in the presence of inhibitors for both trypsin-like and chymotrypsin-like proteases, while the effects of protease inhibitors on sperm velocity were uncertain. Our results indicate similarities in physiology and biochemistry of acrosome between sturgeon and mammals and suggest potential role of protease in the initiation of sperm motility in sturgeon.
Keywords: tosyllysinchlormethylketon; sperma; Tosyllysine Chloromethyl Ketone; Acrosome; neparametrická statistika; spermie; Acrosin; inhibitory proteas; ryby; histologické techniky; Peptide Hydrolases; Sperm Motility; analýza rozptylu; Analysis of Variance; Histological Techniques; zvířata; akrozom; rosanilinová barviva; Rosaniline Dyes; Fishes; motilita spermií; Male; Microscopy, Immunoelectron; akrosin; Tosylphenylalanyl Chloromethyl Ketone; Semen; Statistics, Nonparametric; Spermatozoa; Animals; imunoelektronová mikroskopie; mužské pohlaví; Protease Inhibitors; proteasy; tosylfenylalanylchlormethylketon